Multiple myeloma epidemiology and patient geographic distribution in Canada: A population study. Issue 14 (5th April 2019) - Tsang, Matthew; Le, Michelle; Ghazawi, Feras M.; Cyr, Janelle; Alakel, Akram; Rahme, Elham; Lagacé, François; Netchiporouk, Elena; Moreau, Linda; Zubarev, Andrei; Roshdy, Osama; Glassman, Steven J.; et al.
Abstract : Background: Multiple myeloma (MM) is a malignancy of mature plasma cells. Environmental risk factors identified for this malignancy, among others, include farming and exposure to pesticides. Methods: Using 3 independent population‐based databases (the Canadian Cancer Registry, le Registre Québécois du Cancer, and Canadian Vital Statistics), this study analyzed patients' clinical characteristics and the incidence, mortality, and geographic distribution of MM cases in Canada during 1992‐2015. Results: In total, 32, 065 patients were identified, and 53.7% were male. The mean age at the time of diagnosis was 70 ± 12.1 years. The average incidence rate in Canada was 54.29 cases per million individuals per year, and linear regression modeling showed a steady rise in the annual rate of 0.96 cases per million individuals per year. At the provincial level, Quebec and Ontario had significantly higher incidence rates than the rest of Canada. An analysis of individual municipalities and postal codes showed lower incidence rates in large metropolitan areas and in high‐latitude regions of the country, whereas high incidence rates were observed in smaller municipalities and rural areas. Land use analysis demonstrated increased density of crop farms and agricultural industries in high‐incidence areas. A comparison with the available data from 2011‐2015 showed several consistent trends at provincial, municipal, and regional levels. Conclusions: These results provide a comprehensive analysis of the MM burden in Canada. Large metropolitan cities as well as high‐latitude regions were associated with lower MM incidence. Higher incidence rates were noted in smaller cities and rural areas and were associated with increased density of agricultural facilities. Abstract : Large metropolitan cities as well as high‐latitude regions (north of the 53rd parallel) are associated with lower incidence rates of multiple myeloma. Higher incidence rates are noted in smaller cities and rural areas and are clustered in relatively low‐latitude areas that are largely located within the reported geographic boundaries of fertile cropland in Canada.